Removal of acid and basic dyes from textile wastewater using modified acrylic fibres waste as an efficient adsorbent - Thanaa F. Abdelhafez; Emad K. Radwan; Galal H. Sayed; Eman M. El Khatib; Mohamed F. Nasr; Lamiaa K. El Gabry (Scientific Reports)
Abstract Acrylic fibre waste (AFW) was modified using sodium hydroxide and sodium ethoxide to improve its dye removal capabilities in textile wastewater. The optimization of modification conditions such as time, temperature, pH, and concentration was conducted to maximize adsorption efficiency. Fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscope (SEM) and surface area measurement (BET) were utilized to characterize the unmodified and modified AFW. The AFW modified with Na-ethoxide and pure NaOH or NaOH mixture exhibited more pronounced cracks and pores compared to the unmodified fibres. FTIR analysis show that the conversion of the nitrile group of the unmodified AFW to an amide group after hydrolysis process. The modified AFW samples were tested for the removal all both dyes C.I. Acid Red 182 (AR182) and C.I. Basic Blue 9- methylene blue (MB) from wastewater. The results inducted that the removal percentage of approximately 96% for MB and 45% for AR182 dye at room temperature after 1 h. It was observed that the efficiency of dye removal was higher at lower temperatures. Isotherm studies, including Langmuir and Freundlich models, as well as kinetic studies, were conducted to analyze the adsorption process. The thermodynamic evaluation was estimated.